Electromagnetic scintillation - Wheelon, Albert D. (Cambridge University Press, 2003)
Electromagnetic scintillation describes the phase and amplitude fluctuations imposed on signals that travel through the atmosphere. Providing a modern reference and comprehensive tutorial for this subject, two volumes cover optical and microwave propagation, integrating measurements and predictions at each step of development. The first volume (published September 2001) dealt with phase and angle-of-arrival measurement errors, which are accurately described by geometrical optics. This second volume concentrates on amplitude and intensity fluctuations of the received signal. Also available...Volume I 0-521-80198-2 Hardback